Creating an automated program scheme of power supply management based on technological processes - Amanbaev Nursultan Salamat o‘g‘li (Peerian Journals Publishing, 2024)
As noted in this article, in connection with the increase in the number of electricity generation equipment based on renewable energy sources and the number of consumers of electricity obtained from them, the sources that produce them, the use of software in the management of technological processes and technical systems It is necessary to combine the efficiency of consumers and control units and autonomous energy systems. Due to the uneven production and consumption of electricity from renewable energy sources under the influence of external conditions, for example, wind, solar radiation, etc., renewable energy sources are an In hybrid mode, where conventional alternators must operate, they will need to be backed up using conventional energy. The best way to reduce energy consumption in combination with renewable energy is by automating the technical program. This increases the power of the power source. In this case, the task of creating a tracking inverter that converts direct current into a current, according to the characteristics of the generator, an alternating current appears experimental studies of a direct current inverter. They control the conversion of mode-linked network signals or microcontroller signals based on an automated software system in reference technological processes.
Keywords: Technological processes; technical software system; software scheme